Kajian Pemanfaatan Internet Sebagai Sumber Bahan Ajar Bagi Guru MI Al Madarijut Jakarta - Rudi Hermawan (SAP (Susunan Artikel Pendidikan), 2018)
Along with the advancement of educational technology, the success of teaching activities in schools, especially in elementary schools, is not only determined by the teaching factors originating only from material books, but also by the utilization of information resources from the internet in enriching and expanding the source of teaching materials. The role of teachers in expanding their knowledge is considered very important to be continuously developed and improved. The utilization of the internet can encourage teachers to be more creative in developing innovations in learning materials in classroom. The flexibility of the Internet and its quickness to dynamically produce changes make the values of information and knowledge grow very quickly. It cannot be denied that besides having the positive aspects, the internet has also negative aspects. Therefore, the teachers have to be more aware of the negative and positive impacts of the internet in order to be able to well explain them to the students in the class. The available space on the internet can be also used by teachers to exchange ideas and communicate through e-mail, discussion forums, web blogs and social media. The research will then give the mapping pattern and comparison of the competence of teachers in MI Al Madarijut in using the internet media as an additional source of subject materials.